Penanganan Persekongkolan Tender Pembangunan Jalan Ruas Ngajam – Apulea Segmen Iii Dalam Perkara Nomor 30/Kppu-I/2019 Oleh Komisi Pengawasan Persaingan Usaha (KPPU) Perspektif UU No. 5 Tahun 1999 - Yuditheo Wardana; Hirsanuddin Hirsanuddin (Commerce Law, 2023)
The purpose The purpose of this research is to find out the Principles of Handling Tender Conspiracy in Cases for the Construction of Jalan Ngajam-Apulea Segment III KPPU Decision No.30/KPPU-I/2019, to find out the Handling of Cases of Tender Conspiracy, in particular the Construction of Jalan Ngajam-Apulea Segment III KPPU Decision No.30/KPPU-I/2019, and to find out the Analysis of the Application of the Tender Conspiracy Law in the Construction Case for the Ngajam-Apulea Segment III Road KPPU's Decision No.30/KPPU-I/2019 by KPPU. The type of research used is normative legal research. There are two principles of the approach, namely the Per Se Illegal Approach principle, and the Rule Of Reason Approach principle specifically for Tender Conspiracy using the Rule Of Reason Approach Principle. There are five tages of case handling based on KPPU Regulation No. 1 of 2019: Reports, Preliminary Examination, Follow-up Examination, Decision and Post-Decision. As well as legally proven that there was an alleged violation of Article 22 of the Anti-Monopoly Law by the discovery of several facts, namely the Similarity of IP Addresses, Similarity of Metadata, Similarity of Company Identity, Similarity of Offer Letters, Equipment of Reported Party III which was stated to be owned by Reported Party I in their Bid Documents, Similarity of Quantity and Price Lists in The Offers of the Reported Parties, the Same Unit Price of Wage in the Offers of the Reported Parties, the Same Unit Prices of Materials in the Offers of the Reported Parties, the Same Unit Prices of Mobilization in the Offers of the Reported Parties, and the Offers of Reported Party I Has Expired. In addition, the fact was found that there was a horizontal conspiracy between business actors to arrange to become a tender winner, and a vertical conspiracy between business actors and the Organizing Committee/Party.